2019
DOI: 10.3177/jnsv.65.515
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Fat Content Is Associated with Fasting-Induced Fibroblast Growth Factor 21 Secretion in Mice Fed Soy Proteins

Abstract: Previous studies suggest that circulating fibroblast growth factor 21 (FGF21) levels are elevated in patients with fatty liver, while fasting-induced secretion of FGF21 is lower in obese patients. It has been reported that soy protein prevents hepatic fat accumulation and induces FGF21 secretion. The present study was designed to evaluate the response of circulating FGF21 levels to feeding and fasting in mice fed soy protein-rich diets. For this, C57BL/6J mice were distributed into control, high-fat high-sucro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Moreover, blood samples were collected in clinical practice, which did not examine effects of consumption or skipping of breakfast in patients. It has been reported that FGF21 secretion is induced by nutrients such as low protein diet [ 32 ], fructose [ 33 ], soy protein [ 34 , 35 ]; hence, there is a possibility that this nutrient intake affects circulating FGF21 levels in this study. It is necessary to examine the extent to which these nutrients induce FGF21 secretion in T1DM patients.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, blood samples were collected in clinical practice, which did not examine effects of consumption or skipping of breakfast in patients. It has been reported that FGF21 secretion is induced by nutrients such as low protein diet [ 32 ], fructose [ 33 ], soy protein [ 34 , 35 ]; hence, there is a possibility that this nutrient intake affects circulating FGF21 levels in this study. It is necessary to examine the extent to which these nutrients induce FGF21 secretion in T1DM patients.…”
Section: Discussionmentioning
confidence: 87%
“…Highfat diets (4.6 kcal/g, soy protein 200 g, sucrose 396 g, lard 155.1 g, cellulose 50 g, calcium carbonate 5.5 g, L-cystine 3 g, soybean oil 25 g, dicalcium phosphate 13 g, mineral mix S10026 10 g, potassium citrate monohydrate 16.5 g, vitamin mix V10001 10 g, and choline bitartrate 2 g) were purchased from Research Diets (NJ). 35…”
Section: Measurements Of Energy Expenditure and Oxygen Consumptionmentioning
confidence: 99%
“…Oxygen consumption (VO 2 ), respiratory exchange ratio (the ratio of the volume of CO 2 produced to the volume of O 2 consumed), carbohydrate oxidation, lipid oxidation, and energy expenditure were determined using a gas analysis system as previously described. 34,35 Respiratory exchange ratio values approaching 0.7 are indicative of exclusive fat utilization, whereas exclusive carbohydrate utilization is represented by values close to 1.0. At 72 h after commencement of measurements, mice were subjected to a 30 h fast, and subsequently refed with soy protein-based high-fat diets (40% of calories from sucrose, 40% from fat, and 20% from protein).…”
Section: Measurements Of Energy Expenditure and Oxygen Consumptionmentioning
confidence: 99%
“…In a previous study, single ingestion of beta-conglycinin, a protein isolated from soy beans, induced postprandial FGF21 secretion in mice [ 22 ]. Furthermore, long-term beta-conglycinin intake suppressed high resting level of circulating FGF21, induced adipose tissue thermogenesis, and prevented body fat accumulation in mice fed high fat diets [ 22 , 23 ]. In addition, interventional human studies have demonstrated that beta-conglycinin intake improves metabolic disorders including dyslipidemia [ 24 ] and visceral fat obesity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%